Role of thorium in the Indian nuclear power programme. (November 2017) - Vijayan, P.K.; Shivakumar, V.; Basu, S.; Sinha, R.K.
Abstract: In the context of Indian nuclear power programme, thorium has always had a prominent place due to its unique resource position with large thorium deposits and limited uranium reserves. A three-stage programme has been devised to efficiently utilise the available resources in a sustainable manner. Work on thorium fuel cycle has therefore been carried out right from the inception of Indian nuclear power programme. Engineering scale studies have been carried out on all aspects of the thorium fuel cycle - mining and extraction, fuel fabrication, utilisation in different reactor systems, evaluation of its various properties and irradiation behaviour, reprocessing and recycling. To provide impetus to these studies and to embark on a large-scale programme, the thorium fuel cycle based Advanced Heavy Water Reactor (AHWR) is being developed. The large-scale deployment of thorium based reactors will also require several additional features such as economic competitiveness, practically no impact on public domain, and enhanced safety which has several technological challenges to be overcome. The paper brings out the design aspects of the AHWR besides the ongoing work on other thorium based reactors such as the High Temperature Reactor (HTR) and the Molten Salt Reactor (MSR). Highlights: Thorium is important to Indian nuclear programme due to its unique position with large thorium and modest uranium resources. The advantages and challenges along with experience gained from thorium fuel cycle have been reviewed. India has technology for thorium utilisation aspects covering mining, fuel fabrication, irradiation, & recycle of U 233 fuel. The development of thorium based advanced reactors being pursued in India are briefly described. Industrial-scale demonstration of thorium fuel cycle technology is expected with the launch of AHWR.